FBG sensor strain performance analysis using optisystem software too - Muhammad Imaduddin Mohd Razi; Mohd Rashidi Che Beson; Saidatul Norlyana Azemi; Syed Alwee Aljunid (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Fibre Bragg Grating is an optical fibre that widely use as sensor to sense strain, temperature and pressure. The advantages of FBG sensor are it will not affected by electromagnetic interference which can improve the accuracy of the result and also can be wearable sensor. In this paper, Optisystem software tools are used to analyse the strain performance of FBG sensor for monitoring knee joint movement in rehabilitation process. Single mode FBG with original wavelength of 1550nm are used to get the accurate result because of less attenuation and absorption factor. This project also analysed the wavelength shifted when strain experienced by FBG change. The accuracy of sensor and method of delivering the result are taken into the account. The interrogator are used to display the wavelength shifted by the FBG when there is change in strain experienced by FBG. All of the proposed designed are tested by using simulation software and the wavelength shifted in the simulation are compared to the theoretical value that has been calculated in this project. The development of this system expected to improve the rehabilitation process towards a healthy life.